2015
DOI: 10.1364/ao.54.003613
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field-induced band bending on GaN: in situ effects of electron beam irradiation on time-dependent cathodoluminescence

Abstract: Electron beam bombardment of GaN has been monitored by secondary electron (SE), cathodoluminescence (CL) imaging, simultaneous in situ CL, and specimen current (SC) measurements. Under extreme irradiation conditions, system perturbations, as seen by SE and time-dependent CL, are attributed to internal charge dynamics extending beyond the scanned areas. Under moderate irradiation conditions, the size of affected regions correlates with nominal scanned regions. Time-dependent CL at the near band edge (NBE) revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…These results resonate with earlier findings reporting SE and CL degraded signals beyond the scanned region due to internal charge dynamics. 14 The steady stored charge values in Fig. 5 mostly vary between 150 and 300 10 -8 C for both 10 and 20keV in all these samples in such a way that cannot explain the τ CL or I CLSS progression in Figures 2 and 4 respectively.…”
Section: Stored Charge At Steady State a Time-dependent Charge Injecmentioning
confidence: 88%
See 4 more Smart Citations
“…These results resonate with earlier findings reporting SE and CL degraded signals beyond the scanned region due to internal charge dynamics. 14 The steady stored charge values in Fig. 5 mostly vary between 150 and 300 10 -8 C for both 10 and 20keV in all these samples in such a way that cannot explain the τ CL or I CLSS progression in Figures 2 and 4 respectively.…”
Section: Stored Charge At Steady State a Time-dependent Charge Injecmentioning
confidence: 88%
“…In this work, simultaneous measurements of NBE CL and specimen current (SC) were conducted as a platform to visualize the interplay of optical properties based on diffusion and leakage currents, the former, believed to be responsible of ultimate failure in operational devices. 3,5,14 Earlier work had confirmed that deep level (DL) emissions remained unaffected, 14 and that surficial carbonaceous impurities were not responsible for decreased NBE signals. 18 In this study, only NBE emissions were monitored from the window regions in LEO GaN films; knowingly, where architected devices down perform those built on the LEO regions.…”
Section: Take Down Policymentioning
confidence: 99%
See 3 more Smart Citations